Boosting Competitiveness Through the Alignment of Corporate Social Responsibility, Strategic Management and Compensation Systems in Technology Companies: A Case Study - Núñez-Sánchez, José Manuel; Molina-Gómez, Jesús; Mercade-Mele, Pere; Almadana-Albón, Santiago (MDPI, 2023)
In the turbulent and dynamic post-COVID business environment, strategic management (SM) and corporate social responsibility (CSR) must increasingly adapt to meet the diverse needs of stakeholders and improve outcomes. Within this context, the total compensation (TC) system can play a pivotal role. This study aims to evaluate the importance of the TC system as a human resource management (HRM) tool that is mediated by the organisation’s strategy and a socially responsible factor in organisational behaviour. Our analysis explores various TC policies, including both financial and non-financial elements, and examines their relationship with SM and CSR policies. Using structural equation modelling on a sample of 205 employees from multinational technology companies based in Spain, we demonstrate a stronger relationship between SM and non-financial TC. Additionally, the indirect effect of SM on the social aspect of CSR is notably stronger through non-financial TC. These findings could have profound implications for practitioners, suggesting that the effective implementation of non-financial TC systems can enhance SM and foster socially responsible organisational behaviour. Moreover, aligning SM with CSR policies through robust compensation systems could enable companies to achieve competitive advantages by increasing workforce commitment and engagement.
Keywords: Competencia económica; Strategic Management; Total compensation; Financial remuneration; Non-financial remuneration; Corporate Social Responsibility